2015
DOI: 10.1007/s00244-015-0218-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutant Determination in Killer Whale Scat Samples: Optimization of a Gas Chromatography/Mass Spectrometry Method and Application to Field Samples

Abstract: Biologic sample collection in wild cetacean populations is challenging. Most information on toxicant levels is obtained from blubber biopsy samples; however, sample collection is invasive and strictly regulated under permit, thus limiting sample numbers. Methods are needed to monitor toxicant levels that increase temporal and repeat sampling of individuals for population health and recovery models. The objective of this study was to optimize measuring trace levels (parts per billion) of persistent organic poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Lundin et al [8,50] showed that POPs, namely PCBs, DDTs, and PBDEs, increase in circulation in SRKWs when Fraser River Chinook abundance is lowest, presumably due to increased fat metabolism in response to nutritional stress. Mobilization of contaminants into circulation also occurs during the energetic demands of lactation, with an estimated 70–90% lactation transfer of maternal toxicant burden in primiparous females [51].…”
Section: Discussionmentioning
confidence: 99%
“…Lundin et al [8,50] showed that POPs, namely PCBs, DDTs, and PBDEs, increase in circulation in SRKWs when Fraser River Chinook abundance is lowest, presumably due to increased fat metabolism in response to nutritional stress. Mobilization of contaminants into circulation also occurs during the energetic demands of lactation, with an estimated 70–90% lactation transfer of maternal toxicant burden in primiparous females [51].…”
Section: Discussionmentioning
confidence: 99%
“…Aziz et al, 2017;Quinn et al,2019;Schmidt et al, 2020;Schultz et al,2018). Scat samples in particular can be useful for assessing the health of individuals and populations, as they offer a range of other information, including data on parasite and pathogen presence (Bergner et al, 2019;Cristescu et al, 2019;Weese et al, 2019), diet composition (e.g., via quantitative PCR or DNA metabarcoding - Iversen et al, 2013;Nelms et al, 2019;Ogurtsov, 2018), hormone profiles (Morden et al, 2011;Vynne et al, 2012), and contaminant loads (Lundin et al, 2015(Lundin et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have been completed that document the presence of contaminants in CIB at levels higher than other Alaskan beluga stocks for some contaminant congeners and temporal increases over time for others (Becker et al, 2000;Krahn et al, 2009;Reiner et al, 2011;Hoguet et al, 2013). Pollution is documented as an important factor in two of the three surrogate populations, SLB and SRKW (Lachmuth et al, 2011;Mongillo et al, 2012;Lundin et al, 2015Lundin et al, , 2016. There is a large number of records for both SLB and SRKW populations, n = 44 and n = 25, respectively, that address consequences of pollution such as disease and reproductive failure (e.g., Wasser et al, 2017;Bernier-Graveline et al, 2021).…”
Section: Threats: Pollution (Low)mentioning
confidence: 99%